Concentración De Lactato De Triatletas De Grupos Por Edades Del Departamento Del Quindío (2019)
Objective: To determine the concentration of lactate in triathletes’ groups per ages of the Quindío Department. Methodology: The study was quantitative, exploratory and cross-sectional, in which was developed a sprint test, where the heart rate and blood samples were taken to determine the concentration of lactate in rest, after each transition and ten minutes after to conclude the test. Moreover; we determined the variables of age, height, mass, IMC. Results and conclusion: the evaluated athletes managed normal values taking into account the concentration of lactate, being in an anaerobic sleeping zone (6 to 8 mmol / l). Considering that this sport is of high resistance, the heart rate was increasing in each transition, except this is a high resistance sport race stage, this conduct was progressive according to the effort made by the athlete.